(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
Veronica Gerchman and Sandra Vargas are two Brazilian artists of the same generation who dedicate themselves to the Theater of Animation on different fronts. They are founders of two of the main companies specialized in this language: Cia Truks and Grupo Sobrevento. The text discusses aspects of the personality and artistic career of these two women, bearing in mind the importance of their achievements not only for the development of this language, but for the formation of other women puppeteers. To achieve that goal, the author uses interviews and specific bibliography, in addition to referring to her own experience as a puppeteer / researcher in contact with these artists.